2010
DOI: 10.1002/msj.20207
|View full text |Cite
|
Sign up to set email alerts
|

Medical Therapy for Obesity

Abstract: Obesity results from a prolonged small positive energy imbalance, and treatment needs to reverse this imbalance. Many different diets have been tried to treat obesity, and weight loss occurs with all of them. There is currently no evidence that supports the superiority of one macronutrient composition for diets over any other. The principal effect seems to be the degree of adherence to the prescribed calorie reduction. Obesity drugs have been developed that tap brain mechanisms for controlling feeding and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Those include male gender and younger age [9], and greater muscle mass [10,11]; conversely, patients with medical comorbidities, a history of repeated attempts at losing weight and with weight cycling, as well as those treated with drugs which induce weight gain, have a lower probability to succeed [6,7,12]. In contrast with the above mentioned results, Jackson et al [13] in a recent study found that being female, heavier and older predicted weight loss in the Health and Retirement Study (performed in the United States), whereas the same predictors did not reach statistical significance in the English Longitudinal Study of Ageing.…”
Section: Introductionmentioning
confidence: 98%
“…Those include male gender and younger age [9], and greater muscle mass [10,11]; conversely, patients with medical comorbidities, a history of repeated attempts at losing weight and with weight cycling, as well as those treated with drugs which induce weight gain, have a lower probability to succeed [6,7,12]. In contrast with the above mentioned results, Jackson et al [13] in a recent study found that being female, heavier and older predicted weight loss in the Health and Retirement Study (performed in the United States), whereas the same predictors did not reach statistical significance in the English Longitudinal Study of Ageing.…”
Section: Introductionmentioning
confidence: 98%
“…With the marked increase in the prevalence of obesity in adults, adolescents and children, it has become more important to identify and characterize novel therapeutic targets to preserve organ function in the face of obesity. Nonetheless, the currently available therapeutic regimens for obesity and diabetes, such as pharmacological treatment, caloric restriction and exercise, have had somewhat limited success . Thus, it is necessary to identify novel effective drugs to better manage multiple organ damage in uncorrected obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment of obesity should ensure a long-term sustainable weight loss, possibly positively influence metabolic disorders that cause the development of obesity [7,8]. The aim of the work is to show effectiveness of orlistat and phentermine in outpatient obesity management and to emphasize that pharmacotherapy for obesity is an integral part of the complex therapy of this serious disease.…”
Section: Introductionmentioning
confidence: 99%